Mushroom Management Approach and Nursing - Fatma Demirkaya (Association of Nurse Managers, 2023)
Mushroom management is an approach that has just begun to be researched and is defined by the metaphor of growing mushrooms. In mushroom cultivation, mushrooms are grown in a dark environment by giving as much heat and air as necessary. Just like in mushroom cultivation, it is a management approach where managers only provide the necessary environment for their employees to perform their duties, do not share any information other than that, expose their employees to the darkness similar to mushrooms, and inform them only when needed. Organizational commitment, decrease in work motivation and performance, distrust of management, burnout, job stress and increase in cynicism are observed in employees exposed to mushroom management style. Although there is no study on the mushroom management style in the management of nursing services, it is estimated that the mushroom management style is used based on the results of the study that there are problems in participation in the decisions and the performance criteria are not shared with the employees. The purpose of this compilation study; to raise awareness about mushroom management and to make inferences about the place of mushroom management in nursing management.